2007
DOI: 10.1111/j.1399-5618.2007.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Agomelatine adjunctive therapy for acute bipolar depression: preliminary open data

Abstract: These results indicate the effectiveness of agomelatine 25 mg in the treatment of depressed bipolar I patients co-medicated with lithium or valpromide. A randomized controlled trial is planned to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(69 citation statements)
references
References 28 publications
2
67
0
Order By: Relevance
“…Melatoninergic effects have recently emerged as a potential target for bipolar disorder [4] and a component of treatment with the antidepressant agomelatine, a MT1 and MT2 agonist with 5HT-2C antagonist properties [5] . One case series of agomelatine added to mood stabilizers for 21 patients with bipolar depression resulted in 81% responding, with 3 patients becoming manic [6] . Melatonin 3 mg added to mood stabilizers was found effective for resistant insomnia in 11 cases who had mania [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Melatoninergic effects have recently emerged as a potential target for bipolar disorder [4] and a component of treatment with the antidepressant agomelatine, a MT1 and MT2 agonist with 5HT-2C antagonist properties [5] . One case series of agomelatine added to mood stabilizers for 21 patients with bipolar depression resulted in 81% responding, with 3 patients becoming manic [6] . Melatonin 3 mg added to mood stabilizers was found effective for resistant insomnia in 11 cases who had mania [7] .…”
Section: Discussionmentioning
confidence: 99%
“…36 Its efficacy in depression in bipolar I patients, in combination with either lithium or valproate, has also been assessed in an open-label study ranging from 6-46 weeks. 37 In addition, it has been suggested that agomelatine may show efficacy in the long-term maintenance treatment of alcoholism, to prevent alcohol-related brain damage. 38 Other areas of research include its use as an adjunct in autism and benzodiazepine withdrawal.…”
Section: Other Disordersmentioning
confidence: 99%
“…In patients with seasonal affective disorder, 25 mg of agomelatine over 14 weeks was associated with significant improvements in the Structured Interview Guide for the HAM-D, with a particular improvement in sleep disturbance and daytime fatigue [Pjrek et al 2007]. Adjunctive use in patients with bipolar type 1 disorder also showed improvement in HAM-D scores [Calabrese et al 2007] and the risk of triggering a manic switch was similar to that seen with venlafaxine [Calabrese et al 2007]. This small study involved 21 patients with type I bipolar disorder who were prescribed concurrent mood-stabilizing agents (either lithium or valporic acid).…”
Section: Introductionmentioning
confidence: 99%